Organotin compounds in Brachidontes rodriguezii mussels from the Bahía Blanca Estuary, Argentina - Quintas, Pamela Yanina (2017)
Levels of tributyltin and its breakdown compounds, including the first record of monobutyltin (MBT) in history for Latin America, were determined in native mussels (Brachidontes rodriguezii) by means of CG-MS, after extraction/derivatization assisted by ultrasound. The samples were collected in 2013 in Bahía Blanca Estuary (Argentina) at 6 sites, which reflect different levels of maritime activities. Total butyltins (TBts = TBT+ DBT+ MBT) levels ranged from 19.64 to 180.57 ng Sn g−1 dry weight. According to the Oslo-Paris commission, the results indicated that 73.9% of mussels could be under biological effects risks associated with TBT pollution. In accordance with the calculated bioaccumulation factors, approximately 56% of samples appeared to have accumulated TBT through the sediments. All sampling sites were shown to be impacted by organotin compounds (OTCs) showing variable levels through seasons, which could be related with the variation of the water temperature. Degradation index analyses suggested aged inputs of TBT possibly under a general degradation process at the area of study. In addition, the occurrence of DBT and MBT could not be uniquely attributed to the degradation pathway of the TBT; in fact, results outlined the possible contribution of some punctual and diffuse sources at the area such as proximity to plastic industries, industrial effluents, sewage outlets and domestic wastewaters.